PENDEKATAN HERMENEUTIK DALAM STUDI ISLAM - Abdulloh Labib (Qolamuna : Jurnal Studi Islam, 2022)
This article aims to explain and provide insight that hermeneutics is one of the approach or theory that can help someone to understand the text of the scriptures. the presence of hermeneutics is also very influential on Islamic studies which basically have the nuances of "multi-interpretation". The hermeneutic approach in Islamic studies, especially as a new alternative in interpreting the meaning of the verses of the Qur'an, should be understood as a way to bring out a deeper meaning from the verses of the Qur'an. In addition, the hermeneutic approach has its own characteristics and gives rise to great hermeneutic figures in Islam and their works have different principles on a meaning and language to be achieved in order to explain the intent of a text from the author with a clearer and better understanding. Keywords: Hermeneutics, Interpretation, Approach, Islamic Studies